Phenotyping of subjects for large scale studies on patients with IBS - Boeckxstaens, Guy; Niesler, Beate (Neurogastroenterology and motility, 2016)
Background Irritable bowel syndrome (IBS) is a complex condition with multiple factors contributing to its aetiology and pathophysiology. Aetiologically these include genetics, life-time events and environment, and physiologically, changes in motility, central processing, visceral sensitivity, immunity, epithelial permeability and gastrointestinal microflora. Such complexity means there is currently no specific reliable biomarker for IBS, and thus IBS continues to be diagnosed and classified according to symptom based criteria, the Rome Criteria. Carefully phenotyping and characterisation of a ‘large’ pool of IBS patients across Europe and even the world however, might help identify sub-populations with accuracy and consistency. This will not only aid future research but improve tailoring of treatment and health care of IBS patients. Purpose The aim of this position paper is to discuss the requirements necessary to standardize the process of selecting and phenotyping IBS patients and how to organise the collection and storage of patient information/samples in such a large multi-centre pan European/global study. We include information on general demographics, gastrointestinal symptom assessment, psychological factors, quality of life, physiological evaluation, genetic/epigenetic and microbiota analysis, biopsy/blood sampling, together with discussion on the organisational, ethical and language issues associated with implementing such a study. The proposed approach and documents selected to be used in such a study was the result of a thoughtful and thorough four-year dialogue amongst experts associated with the European COST action BM1106 GENIEUR (www.GENIEUR.eu).
Gesehen am 14.05.2020